2020
DOI: 10.1002/jcp.29803
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stromal cells; a new horizon in regenerative medicine

Abstract: In recent decades, mesenchymal stromal cells (MSCs) biomedical utilizing has attracted worldwide growing attention. After the first report of the human MSCs obtaining from the bone marrow (BM) tissue, these cells were isolated from wide types of the other tissues, ranging from adipose tissue to dental pulp. Their specific characteristics, comprising self‐renewality, multipotency, and availability accompanied by their immunomodulatory properties and little ethical concern denote their importance in the context … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 212 publications
0
42
0
1
Order By: Relevance
“…Today, the major and most well-known sources of MSCs are BM, AT, and UC; however, they can be isolated from dental pulps (DP), endometrium, peripheral blood (PB), skin, placenta (PL), synovial fluid (SF), muscle, Wharton's jelly (WJ), etc. [4]. MSCs can supposedly be isolated from any human tissue, while there exist concrete restrictions based on the availability of source tissues and invasiveness of the isolation procedures and also different donor's features.…”
Section: Sources Of Mesenchymal Stem/stromal Cells (Mscs)mentioning
confidence: 99%
See 1 more Smart Citation
“…Today, the major and most well-known sources of MSCs are BM, AT, and UC; however, they can be isolated from dental pulps (DP), endometrium, peripheral blood (PB), skin, placenta (PL), synovial fluid (SF), muscle, Wharton's jelly (WJ), etc. [4]. MSCs can supposedly be isolated from any human tissue, while there exist concrete restrictions based on the availability of source tissues and invasiveness of the isolation procedures and also different donor's features.…”
Section: Sources Of Mesenchymal Stem/stromal Cells (Mscs)mentioning
confidence: 99%
“…They showed that these cells were separate from the hematopoietic cells because of dissimilarities in the capability to adhere to the tissue culture vessels and the fibroblast-like morphology of their progeny in culture [2,3]. Friendenstein et al offered a prominent advance by demonstrating that the expansion of BM cell suspensions at clonal density led to the creation of separate colonies that originated from single cells (the colony-forming unit-fibroblasts, CFU-Fs) [4]. Though exclusive characteristics quoted for MSCs vary among specialists due to the lack of a generally accepted surface marker phenotype, all suggested that MSC's populations show plastic adherent property along with the expression of CD73, CD90, and CD105 in the absence of hematopoietic markers, most importantly, CD45, CD34, CD14, CD19, and CD3 [5].…”
Section: Introductionmentioning
confidence: 99%
“…Mesenchymal stem/stromal cells (MSCs) are unique cell populations showing a large potential for unrestricted self-renewal, differentiating into a wide variety of diverse cell lines and forming distinct colonies [1][2][3]. They are multipotent fibroblast-like stem cells typically found in a variety of human tissue, including bone marrow (BM), adipose tissue, liver, intestine, lung, connective muscle tissue, spleen, skin, placenta, umbilical cords, and other tissues [4][5][6]. Currently, excellent progress has been established in stem cell technology with promising therapeutic possibilities for the treatment of various diseases [7].…”
Section: Introductionmentioning
confidence: 99%
“…For the therapeutic application of artificial vascular tissues, use of autologous cells for transplantation is a reasonable strategy to avoid host rejection. Autologous mesenchymal stem / stromal cells (MSCs) are effective biomaterials for constructing tissue allowing successful engraftment [11]. In particular, adipose tissue-derived stromal cells (ASCs) are considered as an attractive biomaterial because the adipose tissue isolation from the donors or patients is minimally invasive.…”
Section: Introductionmentioning
confidence: 99%